Heterotaxy syndrome, dextrocardia, ureteropelvic obstruction, endometriosis, and pulmonary hypertension in an adult with congenital heart defects: a case report - Ahmad Al-Bitar; Mhd Ammar Zalzaleh; Hussien Al Helbawi; Mohammad Hossein Morteza (Journal of Medical Case Reports)
Abstract Background Heterotaxia is characterized by an abnormal positioning of the thoracic and/or abdominal organs, resulting in various physiological and hemodynamic implications. Congenital heart disease involves structural irregularities in the heart or major vessels within the chest, leading to functional challenges. Case presentation We present a 26-year-old Arab female patient with a complex medical history involving heterotaxy, dextrocardia, congenital heart disease, and ureteropelvic junction obstruction diagnosed in her first year of life, followed by the identification of endometriosis in her early twenties. This combination of disorders is reportedly unique in existing literature. The patient sought emergency care for severe diffuse abdominal pain unrelated to diet or bowel movements, accompanied by nausea. The pain was localized in specific areas and radiated to the shoulder. Despite treatment attempts with hormonal therapy for abdominal pain relief, her symptoms persisted. Upon examination, no immediate surgical or medical emergencies were noted, leading to symptom management with antispasmodics and recommendations for specialist follow-ups. The patient’s cardiac condition, including cyanosis and related complications, was discussed along with her past surgeries and diagnostic findings related to her cardiovascular health. Conclusion This case emphasizes the challenges of managing complex medical conditions in a young individual, highlighting the need for multidisciplinary care and long-term follow-up to ensure the best possible quality of life for the patient. An interdisciplinary approach is crucial for the comprehensive care of patients with heterotaxy, as they may present with a wide range of anatomical abnormalities affecting different organ systems. Clinicians need to be well informed about the complexities of heterotaxy syndromes and their diverse manifestations to provide effective and personalized care.